A green synthesis and antibacterial activity of ferrocene-based thiazole derivatives in choline chloride/glycerol eutectic solvent. Issue 34 (9th August 2022) - Zhao, Di; Liu, Yanying; Li, Yang; Chen, Yu
Abstract : A green and effective Hantzsch thiazole synthesis of structurally intriguing ferrocene-based derivatives employing the eutectic mixture choline chloride/glycerol (1 : 2 molar ratio) as a sustainable solvent is described. Abstract : In this work, a green Hantzsch synthesis of 4-ferrocenylthiazole derivatives has been accomplished successfully. The Hantzsch reaction between bromoacetylferrocene and various aryl thioureas, 1-alkylindole-3- or 9-alkylcarbazole-3-carbothioamides proceeded efficiently in a deep eutectic solvent (DES) that is, choline chloride/glycerol (ChCl/Gly) (1 : 2 molar ratio) at 80 °C, avoiding the use of common volatile organic solvents. Moreover, the DES media could be reused up to three times without any appreciable decrease in the yield. The synthetic strategy has the attractive features such as mild and environmentally benign reaction conditions, experimental simplicity, easy work-up procedure and good yields. Subsequently, a preliminary screening for in vitro antibacterial activities of all these newly-synthesized compounds revealed that the halo-substituted (F, Cl, Br) compounds 3f–h showed significant antibacterial activities against Gram (+) bacterial B. subtilis and Gram (−) E. coli, among which the fluoro-substituted 3f possessed the best activity with the MIC value of 7.8125 μg mL −1, being higher than the reference drug ciprofoxacin (15.625 μg mL −1 ).